Kajian Bentuk dan Makna Syair Lagu Tenang Ende Geong Karya Efrem Jaru Manggarai Nusa Tenggara Timur - Dionisius Redemptus Jiri (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2025)
The art of music is a sound that is arranged in such a way that it contains rhythm, song, tone, and harmony, especially from the sound produced by instruments that can produce rhythm. This thesis is titled "A Study of the Form and Meaning of the Poetry of the Song Tenang Ende Geong by Efrem Jaru Manggarai East Nusa Tenggara". In this study the author uses a qualitative method. As for the problem that is researched, namely (1) What is the form of the song Tenang Ende Geong by Efrem Jaru Manggarai East Nusa Tenggara? (2) What is the meaning of the lyrics of the song Tenang Ende Geong by Efrem Jaru Manggarai East Nusa Tenggara, and its relaction in daily life?. The purpose of this research is to find out the Form and Meaning of Poetry in the song Tenang Ende Geong by Efrem Jaru in Manggarai East Nusa Tenggara. In the results of the analysis of the form and meaning of the lyrics of the song Tenang Ende Geong by Mr. Efrem Jaru, it is formed from musical elements supported by (sound, rhythm/rhythm, birama, harmony, melody, tempo, scale, dynamics, timbre, and expression) to form a very beautiful song. Based on the results of the researcher's interview, it can be concluded that Tenang Ende Geong's song has beauty and meaning, both from the language style, song lyrics, and the message conveyed by the songwriter that can be felt by listeners or connoisseurs of Tenang Ende Geong songs. In essence, the content and therefore of the song Tenang Ende Geong tells about a child's longing for a mother who has passed away.